The tardigrade cuticle - Czerneková Michaela; Vinopal Stanislav (Limnological Review, 2021)
Tardigrades (phylum Tardigrada) are aquatic microecdysozoans that have adapted to survive extreme conditions through the formation of cysts or ametabolic tuns. Their body is covered by a cuticle that plays an important role in their life cycle, including their response and adaptation to environmental challenges. Cuticular characteristics are a critical component of tardigrade taxonomy. Therefore, research has often been focused on the relationship between cuticular morphology and ultrastructure and the evolutionary and phylogenetic positioning of the phylum and individual species herein. However, a deeper insight into the ultrastructural characteristics and chemical composition of the tardigrade cuticle is needed. This knowledge is important not only for a better understanding of tardigrade physiology and ecology but also for the development of efficient microinjection and/or electroporation techniques that would allow for genetic manipulation, opening new avenues in tardigrade research. Here, we review data on cuticle ultrastructure and chemical composition. Further, we discuss how the cuticle is affected during moulting, encystment, cyclomorphosis, and anhydrobiosis. Our work indicates that more systematic studies on the molecular composition of the tardigrade cuticle and on the process of its formation are needed to improve our understanding of its properties and functions.